The resolution of the suspect - Azulai, Ariʾelah 1962- (Peabody Museum Press, 2016)
Miki Kratsman (born 1959) has worked as a photojournalist in the Palestinian Occupied Territories for over three decades. Originally created in the context of daily news, his photographs look at both "wanted men"--Individuals sought by the Israeli state--and the everyman and everywoman on the street who, by virtue of being Palestinian in a particular time and place, can be seen as a "suspect." Kratsman has also provoked long-term interaction around the images on social media, creating a Facebook page on which viewers are invited to identify the individuals portrayed and comment on their "fate." This complex project is chronicled in this book in more than 300 images that powerfully implicate the viewer. A text by Ariella Azoulay explores the ways in which the shadow of death is an actual threat that hovers over Kratsman's subjects, and a supplemental booklet contains hundreds of portraits and evocative messages from Kratsman's Facebook project